Development of the Gambling Disorder Identification Test: Results from an international Delphi and consensus process. Issue 2 (21st November 2020) - Molander, Olof; Volberg, Rachel; Månsson, Viktor; Sundqvist, Kristina; Wennberg, Peter; Berman, Anne H.
Abstract: Objectives: Diverse instruments are used to measure problem gambling and Gambling Disorder intervention outcomes. The 2004 Banff consensus agreement proposed necessary features for reporting gambling treatment efficacy. To address the challenge of including these features in a single instrument, a process was initiated to develop the Gambling Disorder Identification Test (GDIT), as an instrument analogous to the Alcohol Use Disorders Identification Test and the Drug Use Disorders Identification Test. Methods: Gambling experts from 10 countries participated in an international two‐round Delphi ( n = 61; n = 30), rating 30 items proposed for inclusion in the GDIT. Gambling researchers and clinicians from several countries participated in three consensus meetings ( n = 10; n = 4; n = 3). User feedback was obtained from individuals with experience of problem gambling ( n = 12) and from treatment‐seekers with Gambling Disorder ( n = 8). Results: Ten items fulfilled Delphi consensus criteria for inclusion in the GDIT ( M ≥ 7 on a scale of 1–9 in the second round). Item‐related issues were addressed, and four more items were added to conform to the Banff agreement recommendations, yielding a final draft version of the GDIT with 14 items in three domains: gambling behavior, gambling symptoms and negative consequences. Conclusions: This study established preliminary construct and face validity for the GDIT.